2012
DOI: 10.1002/app.38632
|View full text |Cite
|
Sign up to set email alerts
|

Wettability alteration of gas condensate reservoir rocks to gas wetness by sol–gel process using fluoroalkylsilane

Abstract: Natural gas is becoming a very important energy source in recent years. A sharp reduction has been observed in gas deliverability in many low permeability gas reservoirs due to bottom‐hole pressure drops below the dew point pressure. It is an established fact that altering the wettability of reservoir rocks from liquid wetness to gas wetness could improve the gas deliverability. In this study, a new polymeric surfactant coating for altering the wettability of Sarkhun reservoir rocks was prepared by using a sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…In view of the widespread applications of wetting phenomena, the studies dealing with the influence of surfactants on the wettability of PTFE and PMMA are important [10 -16] . For examples, Szymczyk et al [10 -11] reported that the adsorption of CTAB and CPyB mixtures at air-liquid is the same as that at PTFE-liquid but is considerably higher than that at PMMA-liquid interface; in addition, the interaction across PTFE-solution interface was Page 6 of 30 A c c e p t e d M a n u s c r i p t 4 largely of Lifshitz-van der Waals type. Harkot et al [12] showed that there was a linear relationship between adhesion tension and the surface tension of not only cationic but also anionic surfactants.…”
Section: Introductionmentioning
confidence: 97%
“…In view of the widespread applications of wetting phenomena, the studies dealing with the influence of surfactants on the wettability of PTFE and PMMA are important [10 -16] . For examples, Szymczyk et al [10 -11] reported that the adsorption of CTAB and CPyB mixtures at air-liquid is the same as that at PTFE-liquid but is considerably higher than that at PMMA-liquid interface; in addition, the interaction across PTFE-solution interface was Page 6 of 30 A c c e p t e d M a n u s c r i p t 4 largely of Lifshitz-van der Waals type. Harkot et al [12] showed that there was a linear relationship between adhesion tension and the surface tension of not only cationic but also anionic surfactants.…”
Section: Introductionmentioning
confidence: 97%
“…Li et al (2011) developed a new and inexpensive chemical with sufficient stability at high temperatures, capable of increasing the gas-and water-phase relative permeability. Sharifzadeh et al (2013) prepared a new polymer surfactant coating using a sol-gel process which was able to enhance the liquid repellency of the solid surfaces. Recently, Feng et al (2012) synthesized a fluorine-containing, acrylate co-polymer emulsion by a cost-effective method, with reasonable capability to increase the gas wetting nature of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they demonstrated that wettability alteration had substantial effect on improving liquid mobility and gas productivity of treated rocks. Several other experimental studies have been also performed on wettability alteration of different rock types (to gas-wetness) using surfactants or fluoro-chemical polymers/surfactants [8][9][10][11][12][13][14]. However, some of these chemicals declared not to be cost-effective or environmentally friendly.…”
Section: Introductionmentioning
confidence: 96%